Study of structural and optical properties of nanostructured wide band gap ternary alloy semiconductor. - Hassan, Zainuriah (Universiti Sains Malaysia, 2015)
Semiconductor technology has continuously progressed from the use of elemental semiconductors such as silicon and germanium to the use of binary, ternary and higher order alloys, particularly of II I-V and II-VI compounds. The interest in these semiconductor alloys stems from the desire to control the energy bandgap, and also to engineer the lattice parameter of the substrate to match that of the epitaxial layer.